2015
DOI: 10.1183/09031936.00156714
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of right ventricular diastolic stiffness in pulmonary hypertension

Abstract: Right ventricular (RV) diastolic stiffness is increased in pulmonary arterial hypertension (PAH) patients. We investigated whether RV diastolic stiffness is associated with clinical progression and assessed the contribution of RV wall thickness to RV systolic and diastolic stiffness.Using single-beat pressure-volume analyses, we determined RV end-systolic elastance (Ees), arterial elastance (Ea), RV-arterial coupling (Ees/Ea), and RV end-diastolic elastance (stiffness, Eed) in controls (n=15), baseline PAH pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
93
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 152 publications
(104 citation statements)
references
References 25 publications
8
93
3
Order By: Relevance
“… 2 More recently, we demonstrated that increased RV diastolic stiffness is associated with worse outcome in patients with PAH. 3 Therefore, diastolic dysfunction is likely to be of clinical relevance. Whether RV diastolic stiffness is restricted to idiopathic pulmonary arterial hypertension or is also present in other disorders that are associated with elevated RV pressure is currently unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 More recently, we demonstrated that increased RV diastolic stiffness is associated with worse outcome in patients with PAH. 3 Therefore, diastolic dysfunction is likely to be of clinical relevance. Whether RV diastolic stiffness is restricted to idiopathic pulmonary arterial hypertension or is also present in other disorders that are associated with elevated RV pressure is currently unclear.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Although it is known for some years that RV systolic adaptation is of clinical importance, it has just recently became clear that RV diastolic stiffness increases and may contribute to disease progression in PAH. 2 , 3 In addition, we have previously shown that RV diastolic stiffness was closely associated with a doubling in sarcomere-derived cardiomyocyte stiffness and increased myocardial fibrosis in end-stage PAH patients. 2 , 4 …”
mentioning
confidence: 99%
“…Coupling of RV function to afterload has an inevitable diastolic component (2,161,182). Diastolic stiffness may be a predictor of outcomes in severe PH (183,184). Please see the online supplement for a summary of RV diastolic function assessment.…”
Section: Assessment Of Rv Diastolic Functionmentioning
confidence: 99%
“…RV end-diastolic elastance or stiffness is emerging as an important clinical predictor of outcomes. An increase in RV diastolic stiffness significantly associates with increased mortality and lung transplantation in patients with pulmonary hypertension [10,15]. A significant decrease in RV diastolic stiffness has been found in patients on 3 months of intravenous prostacyclin therapy PAH [16].…”
mentioning
confidence: 99%
“…A significant decrease in RV diastolic stiffness has been found in patients on 3 months of intravenous prostacyclin therapy PAH [16]. These clinical methods to assess RV diastolic stiffness rely on invasive assessments of RV diastolic pressure and the use of the single-beat method [10,15,17], whereas venous backflow fraction can be measured non-invasively using CMR alone. Few studies have addressed the "veno-atrial" interactions but recent work investigates the role of right atrial function in PAH using echocardiography and CMR imaging [18][19][20][21].…”
mentioning
confidence: 99%